Narrativas de professores: sentido das trajetórias de formação continuada na educação infantil - Novais, Ruslane Marcelino de Mello Campos (2018)
This research is part of the field of continuing teacher education and was developed in the context of Early Childhood Education, focusing on a project promoted by a municipal education network from 2002 to 2016. As a general objective, it seeks to understand the senses attributed by teachers to their training path, articulated to their participation in this project. With this purpose, it is envisaged to discover the elements considered by the subjects as remarkable in this training process, as well as to analyze the formative paths experienced by the teachers involved in the process. Anchored in Bakhtinian theoretical-methodological references, the study undertaken is of a qualitative nature and is inserted in studies with (auto)biographical approach, and uses the Narrative Methodology. The research interlocutors are the female teachers who experienced the training project both as participants and as trainers. The methodological procedures adopted were the application of a questionnaire to the participants of the research in order to make up the group profile; the conversations with the subjects; and the search for records related to the selected training project that would aid in the narrative of this History experienced collectively. As results of the study developed, the senses found in the dialogue with the narratives of the teachers (participants and trainers) affirm the relevance of continuing education, justified by various motivations. They also point out in an analysis of its organicity, the validation of the institution of Early Childhood Education as a privileged locus for continuing education, but they highlight the need for investment in other out-of-school opportunities, enabling a different dialogue with diverse subjects. Therefore, the understood senses enunciate a continuous training that contains multiple configurations and senses, and also point out that its building process is increasingly being shared with the teacher.